Effectiveness of pneumococcal vaccination on hospitalization and death in the adult and older adult diabetic population: a systematic review - Marco Del Riccio; Sara Boccalini; Claudia Cosma; Gabriele Vaccaro; Benedetta Bonito; Beatrice Zanella; Cristina Salvati; Duccio Giorgetti; Lisa Rigon; Massimiliano Alberto Biamonte; Matteo Monami; Paolo Bonanni; et al. (Taylor & Francis Group, 2023)
ABSTRACTIntroduction Diabetic patients are at a higher risk of getting pneumococcal disease and are therefore recommended to get vaccinated. The aim of our systematic review is the retrieval and analysis of all available evidence on the effect of pneumococcal vaccination on the risk of hospitalization and death in adult patients with diabetes.Research design and methods MEDLINEand EMBASE were searched from inception until January 2023. We included all studies investigating whether pneumococcal vaccination reduces the risk of dying or being hospitalized in diabetic patients. The Newcastle-Ottawa scale was used to assess risk of bias. Results Only two studies, encompassing a total of 68,246 subjects, were considered eligible for inclusion and of high quality. In both studies polysaccharide pneumococcal vaccination was associated with a reduction of the risk of hospitalization or death in adult diabetic patients (aHR: 0.76 in one study, aOR: 0.97 in the other one). However, in neither of the two included studies the lower risk was statistically significant.Conclusions Further research is needed due to the potentially major clinical implications for diabetic patients. The results of this systematic review can serve as a foundation for future studies, indicating the importance of continuing research in this area to improve patient outcomes.